TRADITIONAL WORK CULTURE OF ANGAMI-NAGA AT KIGWEMA VILLAGE UNDER KOHIMA DISTRICT, NAGALAND - Thorie, Vizotuo (International Journal of Research -GRANTHAALAYAH, 2024)
The Angami-Naga community follows a unique practices and traditions which have been passed on from the forefathers from generation to generation. Likewise every village has its own ways of practicing the tradition in different ways throughout the year. The people of Kigwema village under Kohima district of Nagaland has their own oral narratives which has been passed on down to the generations about its identity, stories, histories, practice, festivals, and the work culture followed in the year. The village has its rich traditions, follows the “Nanyü” whose translation is customs on different occasions during the particular time of the year after different completions or starting of any kind of work or practice. It also have its moral code of conduct which is called “Kenyü” its meaning is prohibition where the people are not allowed to do or practice certain work or go out during its application. However, the rich culture has been forgotten and ignored in the modern generation because of various factors. Therefore, the objective of the study is to preserve the rich cultural ethnicity of the fast forgotten practices and traditions and carry forward the good deeds followed maintaining a sustainable environment.